Islamic Ethical Values in Traditional Commerce: A Field Study of Market Traders - Taufik Aris Saputra (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
This study explores the implementation of Islamic business ethics in the transaction practices of traders at the Waru Traditional Market, Waru District, Pamekasan Regency. The research addresses the problem of how Islamic ethical principles—such as tauhid (oneness of God), balance, free will, responsibility, and benevolence (ihsan)—are reflected in the daily commercial behaviors of traditional market traders. The objective is to uncover how deeply these principles are understood and applied in the context of local economic transactions, especially among grassroots Muslim communities. Using a qualitative descriptive method, data were collected through field observation and in-depth interviews with both traders and buyers. The primary data sources were direct interviews with ten selected traders, while secondary sources included relevant literature on Islamic economics and ethics. The findings reveal that most traders apply the main principles of Islamic business ethics in their transactions. The principle of tauhid is evident in their belief that sustenance comes from Allah, prompting them to conduct business with sincerity, patience, and a worshipful spirit. The principles of balance and responsibility are reflected in fair dealings, such as product quality assurance, replacement of defective goods, and price transparency. Traders also practice free will by giving customers full freedom in making purchasing decisions. Moreover, the principle of benevolence (ihsan) is actively demonstrated through acts of kindness, such as granting price discounts, extending payment terms, and assisting with the physical delivery of goods. This study contributes to the understanding of how Islamic values can be operationalized in traditional market settings. It highlights the spiritual and moral dimensions of Islamic business practices and offers a model for building ethical, human-centered, and sustainable local economies rooted in religious principles.